Sclerosing stromal tumor of the ovary: ultrasound elastography and MRI findings on preoperative diagnosis - Onur, Mehmet Ruhi; Simsek, Bengu Cobanoglu; Kazez, Ahmet (Springer Tokyo, 2011)
Sclerosing stromal tumor (SST) is a benign stromal tumor of the ovary. Preoperative diagnosis of this benign tumor mainly depends on imaging findings. Dynamic computed tomography (CT) and magnetic resonance imaging (MRI) show typical contrast enhancement of SST with peripheral enhancement in the early phase and centripetal progression in the delayed phases. We present the imaging findings of ultrasonography, ultrasound elastography, and dynamic MRI in the diagnosis of SST. Abdominal ultrasound elastography is a novel technique that depicts the stromal structure of SSTs by comparing the elasticity of the tumor and the myometrium using quantitative strain values.
Keywords: Ovary; Sclerosing stromal tumor; MR imaging; Ultrasound elastography